Intact Regulatory T-Cell Function but Defective Generation of IL–17A-Producing CD4+ T Cells in XIAP Deficiency. Issue 2 (August 2016) - Gurram, Bhaskar; Hammelev, Erin; Syverson, Grant; Haribhai, Dipica; Yan, Key; Simpson, Pippa; Salzman, Nita; Verbsky, James W.
ABSTRACT: Objective: X-linked inhibitor of apoptosis (xIAP) deficiency is a primary immune deficiency disorder associated with hemophagocytic lymphohistiocytosis. About 17% of xIAP-deficient patients present with very early onset severe colitis with high mortality. We hypothesized that xIAP deficiency leads to defective generation and/or survival of T regulatory cells (Treg ) through its involvement in transforming growth factor-β signaling. Methods and Results: We used a T-cell transfer model of chronic colitis and observed a mild increase in colitis severity induced by naïve CD4 + T cells from xIAP 0/ − mice compared with colitis induced by naïve CD4 + T cells from WT mice. We did not observe any significant difference in the induction of Treg cells in these studies. We next tested whether xIAP is required for Treg cell function by co-transferring xIAP −/0 or WT Treg cells with naïve WT CD4 cells in this model. We demonstrate that XIAP-deficient Treg cells were able to prevent disease similarly to WT Treg cells. In these experiments we, however, found a significantly decreased percentage of IL–17A-producing CD4 + T cells in mice receiving Tregs from xIAP 0/ − mice. Conclusions: xIAP appears dispensable for the generation of induced Treg cells as well as function of natural Treg cells. There appeared to be a role of xIAP in generation of IL–17-producing cells from either naïve CD4 + T cells or Treg cells. Further research is needed to explore the role of xIAP in generation of IL–17-producing cells.